Comparison of average and peak anaerobic power levels by locations in handball - Taskin, C.; Taskin, A. K.; Üzüm, R. Y.; Ak, A. E. (European Journal of Physical Education and Sport Science, 2020)
The aim of this study is: it is thought that researching and knowing the physical characteristics of handball players and their quickness and agility performances according to their playing positions can also be helpful in choosing athletes according to their positions in handball. Research in Turkey handball federation 2. league active handball playing 5 keeper, 10 central playmaker, 5 right quarterback, 5 left playmaker, 5 right, 5 left, and was attended by 5 volunteered a total of 40 male handball players, including pivot. Agility test measurement illionis test was performed. In the speedy test measurement, the test distance is determined as 5 meters. The track consists of 4 slaloms, two at the beginning and two at the end. One photocell is placed at the exit and at the end. When we examine the quickness and agility performances of the athletes in our study; It has been observed that the players playing in the right and left wing players and the right-left playmaker have the best values in their quickness and agility performances, and the players playing in the pivot area have the worst values.